PERANAN KEJAKSAAN DALAM MENANGANI KASUS TINDAK PIDANA KORUPSI DI WILAYAH HUKUM KEJAKSAAN NEGERI PAYAKUMBUH - Failin, Failin; Yuserlina, Anny (Ensiklopedia of Journal, 2025)
Abstract: The Payakumbuh District Attorneys Office has great potential to play a more effective role in eradicating corrupstion. This can be achieved through increasing the capacity of human resources both in terms of quality and quantity of prosecutors, the use of technology in collecting evidence, and better synergy with other law enforcement officers. The success of the Payakumbuh District Attorneys Office in handling corruption cases is not only measured by the number of cases revealed, but also by the ability of this institution to recover state losses and provide a dererrent effect to perpetrators of corruption.Keywods: Role, Prosecutors office, Criminal Acts, Corruption